2016
DOI: 10.1039/c5ra26604a
|View full text |Cite
|
Sign up to set email alerts
|

A novel coupling reaction of α-halo ketones promoted by SmI3/CuI

Abstract: In the presence of SmI3 and catalyzed by CuI in DMF, α-haloketones were transformed unexpectedly into α-hydroxy-1,4-diketones. The mechanism was probed and DMF was assumed to play a dual role both as a hydroxyl source and as a solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Our recent interests in the transition‐metal catalysis in organic transformations brought our attention to the combination of samarium reagents and copper salts. By virtue of the exceptional coupling ability of copper, which was widely used in the construction of new carbon‐carbon bonds and carbon‐hetero bonds, the samarium/copper system has exhibited impressive reactivity to promote novel reactions …”
Section: Methodsmentioning
confidence: 99%
“…Our recent interests in the transition‐metal catalysis in organic transformations brought our attention to the combination of samarium reagents and copper salts. By virtue of the exceptional coupling ability of copper, which was widely used in the construction of new carbon‐carbon bonds and carbon‐hetero bonds, the samarium/copper system has exhibited impressive reactivity to promote novel reactions …”
Section: Methodsmentioning
confidence: 99%
“…Presumably, due to the higher density of acetyl groups in pVPE as compared to PS-Ac, an aldol condensation between neighboring PGA and remaining acetyl groups had occurred during the oxidation reaction, as was described for the oxidation of acetophenone into PGA/PGAH (Scheme 3). 44,45 Because PS was only acetylated for 60%, this side reaction likely also occurred to a smaller extent in this material, as indicated by a very minor peak at 70 ppm in the spectrum of PS-Ac-Ox (Supporting Information Figures S20 and S21).…”
Section: Acs Applied Polymer Materialsmentioning
confidence: 99%
“…In DMF, the SmI 3 /CuI-promoted condensation of α-halo ketones resulted in an unexpected hydroxylation reaction (Scheme 13(a 1 )) [48]. Liu's team demonstrated that the reaction arises via a tribenzoylcyclopropane, which affords the corresponding α-hydroxy-1,4-diketone (Scheme 13(a 2 )) through the participation of two DMF entities (Scheme 13(a 3 )).…”
Section: O Fragmentmentioning
confidence: 99%